The first rector of the republican university in Venezuela: José María Vargas Ponce. - Mora García, José Pascual (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2024)
Objective: Our main objective is to unveil the foundations of the Statutes of the Central University of Venezuela (1827), considered the first republican university in Venezuela. It was sensuataria (sic) of the Real y Pontificia Universidad de Caracas (1721), with its colonial heritage of the old Colegio Santa Rosa de Lima de Caracas. Methodology: It is a study that methodologically is nourished by the historiographic paradigm of the network Society for the History of Latin American Education (Shela), (Soto et al, 2017). Originality: In this sense, it seeks to elaborate a study on the Statutes and educational mentality, with "first hand" documents, documentary survey and application of the dialogic-critical, descriptive method, empowered in the guidelines of the epistemologies of the south. Strategy/Data Collection. The study is followed on the sources of the Acts of the Plenary University Senate, among other points we will address: the state of the art of experimental science; the relation of sanctions or punishments; the commitments of the students and the benefits and norms; the elimination of the figure of the censor regio; the exoneration of military service for students; the elimination of the prejudice of "cleanliness of blood" to enter the university; the process of election of the first republican rector; the pious works as scenarios for the support of the university; the support to the integrity of Colombia; the foundation of the chairs for the teaching of English and French; the consecration of the right of retirement of the professors; the university will watch over as protective board of the Colegio de Niñas Educandas; exoneration of the payments for the right of degree, on the part of the bachelor Medardo Medina, for being of notorious poverty; among other aspects that appear in its Statutes. Conclusions: the republican university was founded on the criteria of modern science, the rights established in the Constitution of 1821, and the emerging principles in labor matters and the university. The intellectual formation and the civil spirit of Venezuelan José María Vargas Ponce (1786-1854), as the first rector, was fundamental to appraise the center of the Enlightenment inspired by the spirit of the Enlightenment.